The new work of educational leaders : changing leadership practice in an era of school reform - Gronn, Peter (Paul Chapman, 2003)
Peter Gronn provides a new framework for understanding leadership practice. The work of leaders will increasingly be shaped by three over-riding themes; design, distribution and disengagement.